IMPLEMENTASI KONSELING INDIVIDU DENGAN TEKNIK EXCEPTION DALAM MENCEGAH PERILAKU BOLOS DI SMK MUHAMMADIYAH PETANAHAN [THE IMPLEMENTATION OF INDIVIDUAL COUNSELING WITH EXCEPTION TECHNIQUE IN PREVENTING TRUANCY BEHAVIOR IN SMK MUHAMMADIYAH PETANAHAN] - Yoan Rachmawati Putri (Journal of Contemporary Islamic Counselling, 2022)
The problems that exist in schools are certainly various, one of which is truancy behavior. With the application of individual counseling services with exception techniques carried out by guidance and counseling teachers in the form of instructions to provide assistance to students who directly conduct individual counseling, So that, students are expected to believe that the student’s absence or truancy behavior is wrong. The purpose of this study was to find out how the implementation of individual counseling used to reduce truant students. This study uses qualitative research methods. The subject of the study was a KA teenager who often skipped school. The results showed that the subject had a problem that ultimately chose to skip school, after counseling the subject gave a significant response and change, he realized that the behavior was not right and tried to change it.